THE IMPACT OF NURSING TEAMWORK ON PATIENT SAFETY AND QUALITY OF CARE IN SAUDI ARABIAN HOSPITALS: A CROSS-SECTIONAL SURVEY - Jawaher Mohammad Aqeel Alshammari, Maha Mubarak Aldhafeeri, Reem Trad Saeed Alenezi, Afaf Kamel Aldhafeeri, Yasamiyan Mubarak Mohammed Aldhafeeri, Huriyyah Mubarak Aldhafeeri (Chelonian Research Foundation, 2022)
Nursing teamwork plays a crucial role in ensuring patient safety and delivering high-quality care in healthcare settings. This study aimed to investigate the impact of nursing teamwork on patient safety and quality of care in Saudi Arabian hospitals. A cross-sectional survey design was employed, and data were collected from a sample of 450 nurses working in three tertiary hospitals in Riyadh, Saudi Arabia. The Nursing Teamwork Survey (NTS) and the Hospital Survey on Patient Safety Culture (HSOPSC) were used to measure nursing teamwork and patient safety culture, respectively. The Quality of Care Scale (QCS) was used to assess nurses' perceptions of the quality of care provided in their units. Descriptive statistics, Pearson's correlation, and multiple linear regression analyses were conducted to examine the relationships between nursing teamwork, patient safety culture, and quality of care. The results revealed a significant positive correlation between nursing teamwork and patient safety culture (r = 0.612, p < 0.001), as well as between nursing teamwork and quality of care (r = 0.548, p < 0.001). Multiple linear regression analysis showed that nursing teamwork was a significant predictor of both patient safety culture (β = 0.587, p < 0.001) and quality of care (β = 0.502, p < 0.001), after controlling for demographic variables. The findings highlight the importance of fostering effective nursing teamwork to enhance patient safety and quality of care in Saudi Arabian hospitals. Recommendations for practice include implementing team-building interventions, promoting interprofessional collaboration, and providing leadership support to create a culture of teamwork and safety. Keywords: nursing teamwork, patient safety, quality of care, Saudi Arabia, cross-sectional survey